Spanish Grammatical Gender Interference in Papiamentu - Jorge R. Valdés Kroff; Frederieke Rooijakkers; M. Carmen Parafita Couto (Languages, 2019)
The aim of this study is to determine whether Spanish-like gender agreement causes interference in speakers of Papiamentu (a Western Romance-lexified creole language) who also speak Spanish. Papiamentu and Spanish are highly cognate languages in terms of their lexicons. However, Papiamentu lacks grammatical gender assignment and agreement, leading to cognate words with major morpho-syntactic differences. A total of 41 participants with different linguistic profiles (Papiamentu-dominant, Dutch-dominant, Spanish-dominant, and Spanish heritage speaker-Papiamentu bilinguals) listened to 82 Papiamentu sentences, of which 40 contained a Spanish-like gender-agreeing element on the Determiner, Adjective, or Determiner + Adjective and with half of the experimental items marked with overtly masculine (i.e., -o) or feminine (i.e., -a) gender morphology. Participants performed a forced-choice acceptability task and were asked to repeat each sentence. Results showed that Spanish-dominant speakers experienced the greatest interference of Spanish gender features in Papiamentu. This suggests that in cases where speakers must suppress gender in their second language (L2), this is not easy to do. This is especially the case in highly cognate languages that differ in whether they realize gender features.